Expressions of Matrix Metalloproteinases (MMP-2, MMP-7, and MMP-9) and Their Inhibitors (TIMP-1, TIMP-2) in Inflammatory Bowel Diseases - Katarzyna Jakubowska; Anna Pryczynicz; Piotr Iwanowicz; Andrzej Niewiński; Elżbieta Maciorkowska; Jerzy Hapanowicz; Dorota Jagodzińska; Andrzej Kemona; Katarzyna Guzińska-Ustymowicz (Gastroenterology Research and Practice)
Crohn’s disease (CD) and ulcerative colitis (UC) belong to a group of inflammatory bowel diseases (IBD). The aim of our study was to evaluate the expression of MMP-2, MMP-7, MMP-9, TIMP-1, and TIMP-2 in ulcerative colitis and Crohn’s disease. The study group comprised 34 patients with UC and 10 patients with CD. Evaluation of MMP-2, MMP-7, MMP-9, TIMP-1, and TIMP-2 expression in tissue samples was performed using immunohistochemistry. The overexpression of MMP-9 and TIMP-1 was dominant in both the glandular epithelium and inflammatory infiltration in UC patients. In contrast, in CD subjects the positive expression of MMP-2 and TIMP-1 was in glandular tubes while mainly MMP-7 and TIMP-2 expression was in inflammatory infiltration. Metalloproteinases’ expression was associated with the presence of erosions, architectural tissue changes, and inflammatory infiltration in the lamina propria of UC patients. The expression of metalloproteinase inhibitors correlated with the presence of eosinophils and neutrophils in UC and granulomas in CD patients. Our studies indicate that the overexpression of metalloproteinases and weaker expression of their inhibitors may determine the development of IBD. It appears that MMP-2, MMP-7, and MMP-9 may be a potential therapeutic target and the use of their inhibitors may significantly reduce UC progression.